PLASMA FATTY ACIDS AND THE RISK OF VASCULAR AND MORTALITY OUTCOMES IN INDIVIDUALS WITH TYPE 2 DIABETES: RESULTS FROM THE ADVANCE STUDY. (April 2021) - Harris, Katie; Oshima, Megumi; Sattar, Naveed; Wurtz, Peter; Jun, Min; Welsh, Paul; Chalmers, John; Woodward, Mark
Abstract : Objective: This study aimed to quantify the association of essential and other plasma fatty acids biomarkers with macrovascular disease, microvascular disease and death in individuals with type 2 diabetes. Design and method: A case cohort study (N = 3, 576), including 654 macrovascular events, 341 microvascular events and 631 deaths during 5 years of median follow-up was undertaken in participants in the Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation (ADVANCE) study. The fatty acids measured from baseline plasma samples, by proton nuclear magnetic resonance (NMR) analysis, were omega-3, docosahexaenoic acid (DHA), omega-6, linoleic acid (LA), polyunsaturated (PUFA), monounsaturated (MUFA) and saturated fatty acids (SFA). Hazard ratios (HRs) were modelled per standard deviation higher percentage fatty acid. C-statistics and net reclassification improvement were used to test the added value of fatty acids for risk prediction. Results: After adjustment for traditional cardiovascular risk factors, an inverse association was observed for omega-3 fatty acids and DHA (HR [95%CI]: 0.87 [0.80, 0.95] and 0.88 [0.81, 0.96], respectively per 1SD higher percentage) with the risk of macrovascular events, and for omega-3 fatty acids (HR [95%CI]: 0.91 [0.84, 0.99] per 1SD higher percentage) with death. Such associations were also evident when investigating absolute levels of fatty acids. There were no statistically significant associations between any fatty acids and microvascular disease after adjustment. However, there was limited improvement in predictive ability of models when any fatty acid was added. Conclusions: Plasma omega-3 fatty acids and DHA were found to be inversely associated with macrovascular disease, whilst omega-3 fatty acids was also inversely associated with death. These results provide additional support for regular consumption of food rich in omega-3 fatty acids in type 2 diabetes.